4D-Printed Magnetic Responsive Bilayer Hydrogel - Yangyang Li; Yuanyi Li; Jiawei Cao; Peng Luo; Jianpeng Liu; Lina Ma; Guo-Lin Gao; Zaixing Jiang (Nanomaterials)
Despite its widespread application in targeted drug delivery, soft robotics, and smart screens, magnetic hydrogel still faces challenges from lagging mechanical performance to sluggish response times. In this paper, a methodology of in situ generation of magnetic hydrogel based on 3D printing of poly-N-isopropylacrylamide (PNIPAM) is presented. A temperature-responsive PNIPAM hydrogel was prepared by 3D printing, and Fe2O3 magnetic particles were generated in situ within the PNIPAM network to generate the magnetic hydrogel. By forming uniformly distributed magnetic particles in situ within the polymer network, 3D printing of customized magnetic hydrogel materials was successfully achieved. The bilayer hydrogel structure was designed according to the different swelling ratios of temperature-sensitive hydrogel and magnetic hydrogel. Combined with the excellent mechanical properties of PNIPAM and printable magnetic hydrogel, 4D-printed remote magnetic field triggered shape morphing of bilayers of five-petal flower-shaped hydrogels was presented, and the deformation process was finished within 300 s.